Type I Interferon Gene Response Is Increased in Early and Established Rheumatoid Arthritis and Correlates with Autoantibody Production - Castañeda-Delgado, Julio E.; Bastián-Hernandez, Yadira; Macias-Segura, Noe; Santiago-Algarra, David; Castillo-Ortiz, Jose D.; Alemán-Navarro, Ana L.; Martínez-Tejada, Pedro; Enciso-Moreno, Leonor; Garcia-De Lira, Yolanda; Olguín-Calderón, Diana; Trouw, Leendert A.; Ramos-Remus, Cesar; et al. (Frontiers in Immunology, 2017)
Rheumatoid arthritis is an inflammatory debilitating disease that affects the joints in the early and productive phases of an individual’s life. Several cytokines have been linked to the disease pathogenesis and are known to contribute to the inflammatory state characteristic of RA. The participation of type I interferon (IFN) in the pathogenesis of the disease has been already described as well as the identity of the genes that are regulated by this molecule, which are collectively known as the type I IFN signature. These genes have several functions associated to apoptosis, transcriptional regulation, protein degradation, Th2 cell induction, B cell proliferation, etc. The present article evaluates the expression of the IFN signature in different stages of disease and their correlation with the levels of antibodies against citrullinated proteins (ACPA) and carbamylated proteins (Anti-CarP). Methods: Samples from individuals with early and established RA, high risk individuals (ACPA+ and ACPA-) and healthy controls were recruited at “Unidad de Artritis y Rheumatismo” (Rheumatism and Arthritis Unit) in Guadalajara Jalisco Mexico. Determinations of ACPA were made with Eurodiagnostica ACPA plus kit. Anti-CarP determinations were made according to previously described protocols. RNA was isolated and purity and integrity determined according to RIN > 6. Gene expression analysis was made by RT-qPCR using specific primers for mRNAs of the type I IFN signature. Relative gene expression was calculated according to (Livak and Schmitgen). Results: Significant differences in gene expression were identified when comparing the different groups for MXA and MXB (p<0.05), also when comparing established RA and ACPA- in both IFIT 1 and G15. Increased expression of ISG15 was identified (p<0.05) and a clear tendency toward increase was identified for HERC5. EPSTRI1, IFI6 and IFI35 were found to be elevated in the cRA and eRA respectively (p<0.05). Significant correlations were identified for the IFN signature genes with the levels of ACPA and Anti-CarP (p<0.05). Conclusion: Our data confirms previous observations in the role of IFN signature and the pathogenesis of RA. Also, we provide evidence of an association between IFN-signature genes (that regulate Th2 cells and B cell proliferation) with the levels Anti-CarP and ACPA autoantibodies.